2018
DOI: 10.5897/ajb2015.14655
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of indigenous sheep breeds in Nigeria based on electrophoretic polymorphous systems of transferrin and haemoglobin

Abstract: The study used 100 indigenous sheep comprising 25 Balami, 25 Uda, 25 Yankassa and 25 West African Dwarf breeds reared extensively. The blood samples were taken from Vena Jugularis, processed according to standard procedure and transferrin and haemoglobin examined using cellulose acetate electrophoresis. The observed allele frequencies and genotypes (%) were tested with Hardy-Weinberg's Equilibrium (χ 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…The finding also agrees with Rodero et al (1996) in Lebrijan Churro breed of Andalusia sheep but not in Merino sheep and Akinyemi and Salako (2010) in WAD sheep. The proportions of the haemoglobin genotypes at 52% HbAA, 22% HbAB and 27% HbBB in this study differ from the 100% HbAA reported by Dafur et al (2019) in WAD sheep; the 72% HbAA and 28% HbAB obtained by Osaiyuwu and Salako (2018) in WAD sheep; the 88.89% HbAA and 11.11% HbAB in WAD sheep obtained by Akinyemi and Salako (2010); the 0.00% HbAA, 11.11% HbAB and 88.89% HbBB in Lebrijan Churro breed of Andalusia sheep and the 17% HbAA, 20.65% HbAB and 77.17% HbBB for the Grazalema Merino sheep reported by Rodero et al (1996). However, the result supports the association of the highest frequency of HbAA in females (Akinyemi and Salako, 2010) and the HbAA genotype being the most frequent in WAD sheep (Osaiyuwu and Salako, 2018).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The finding also agrees with Rodero et al (1996) in Lebrijan Churro breed of Andalusia sheep but not in Merino sheep and Akinyemi and Salako (2010) in WAD sheep. The proportions of the haemoglobin genotypes at 52% HbAA, 22% HbAB and 27% HbBB in this study differ from the 100% HbAA reported by Dafur et al (2019) in WAD sheep; the 72% HbAA and 28% HbAB obtained by Osaiyuwu and Salako (2018) in WAD sheep; the 88.89% HbAA and 11.11% HbAB in WAD sheep obtained by Akinyemi and Salako (2010); the 0.00% HbAA, 11.11% HbAB and 88.89% HbBB in Lebrijan Churro breed of Andalusia sheep and the 17% HbAA, 20.65% HbAB and 77.17% HbBB for the Grazalema Merino sheep reported by Rodero et al (1996). However, the result supports the association of the highest frequency of HbAA in females (Akinyemi and Salako, 2010) and the HbAA genotype being the most frequent in WAD sheep (Osaiyuwu and Salako, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…It is a conjugated protein with two pairs of identical sub-units, each with a cleft that contains ironporphyrin group which is the site of oxygen uptake and release. Osaiyuwu and Salako (2018) found two genotypes of Hb comprising 72% HbAA and 28% HbAB in WAD sheep while Dafur et al (2019) reported 100% HbAA. Mabruka and Ahmed (2018) reported 22% of HbA and 78% of HbB as gene frequencies of alleles A and B in WAD sheep.…”
Section: Introductionmentioning
confidence: 97%